2007
DOI: 10.1016/j.crci.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Review of actinide decorporation with chelating agents

Abstract: In case of accidental release of radionuclides in a nuclear facility or in the environment, internal contamination (inhalation, ingestion or wound) with actinides represents a severe health risk to human beings. It is therefore important to provide effective chelation therapy or decorporation to reduce acute radiation damage, chemical toxicity, and late radiation effects.Speciation governs bioavailability and toxicity of elements and it is a prerequisite tool for the design and success of new ligands or chelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…By the means of chromatographic studies and competition experiments with iron, the authors reported that the binding site of Th(IV) was the iron-binding site of transferrin (HSTf). Similar behaviour was reported for different actinides (IV) including Pu(IV) from various in vivo and in vitro studies [3,[9][10][11]. The interaction between Th(IV) and HSTf was further studied by Harris et al [12] by using difference ultraviolet spectroscopy (DUS).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…By the means of chromatographic studies and competition experiments with iron, the authors reported that the binding site of Th(IV) was the iron-binding site of transferrin (HSTf). Similar behaviour was reported for different actinides (IV) including Pu(IV) from various in vivo and in vitro studies [3,[9][10][11]. The interaction between Th(IV) and HSTf was further studied by Harris et al [12] by using difference ultraviolet spectroscopy (DUS).…”
Section: Introductionmentioning
confidence: 56%
“…The quantitative description of the interactions of thorium (IV) with blood serum components is of high relevance for the rational design of molecules suitable for in vivo chelation of thorium in medical applications [1,2] or for decorporation in case of accidental ingestion [3][4][5]. In the first case, the chelating agent is used to couple the radionuclide to tumor selective carrier molecules to target and destroy cancer cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that running the titrations only up to pH 8.5 and 9.0, respectively, restored reversibility in the uranyl titrations. The cause of this irreversibility is unknown, but corresponds roughly to additional deprotonation of or continued hydroxide introduction to the [UO 2 Uranyl titrations with all Me-3,2-HOPO ligands displayed a rapid increase in intensity between pH 2 and pH 4, indicating deprotonation of the ligand and complexation of the uranyl cation. For tetradentate ligands (with the exception of L 6 H 2 ), this result was refined as the formation of a UO 2 L(solv.)…”
Section: Eqmentioning
confidence: 99%
“…pUO 2 is calculated using standard conditions of [UO 2 2+ ] = 10 -6 M and [L] = 10 -5 M (L:UO 2 2+ = 10), and thus the minimum pUO 2 value is 6.0, at which no metal complexation occurs. While typically reported at physiological pH, pUO 2 can be calculated at any pH once proton and uranyl affinities are known; pUO 2 values at pH 2.5, 7.4 and 8.5 are listed for each Me-3,2-HOPO ligand in Table 4.…”
Section: (L)(oh)] -Complex To Form a [Uo 2 (L)h -2 ] 2-species (Wherementioning
confidence: 99%
See 1 more Smart Citation